Behavior Characterization of Use of Mobile Phones which Potentially Cause Health Problems of Elementary School-Age Children in Rural and Urban Areas - Susi Wahyuning Asih; Ginanjar Sasmito Adi; Supriyadi (Jurnal Kesehatan dr. Soebandi, 2021)
Introduction: The development of communication technology meets a siginificant advancement, and mobile phones are part of it. Mobile phones are used not only by adults but also by children, including elementary school age children. Children in using mobile phones have different behavior based on their social, economic and cultural differences. Some behaviors of children in using mobile phones have a risk of health problems. Objective: The purpose of the study was to characterize the behavior of the use of mobile phones in primary school age children which could potentially cause health problems. Methods: This is a descriptive study using cross-sectional design. The study involved 60 children and their parents in urban and rural elementary schools. Data were collected by questionnaire (there were 13 questions) using the Google form application (close ended questionnaire) from population taken by the nonprobability sampling method. The data obtained were analyzed using descriptive analysis. Results: The results found that the possession of mobile phones, lighting, place and duration of use mobile phones were behaviors that descriptively showed that there were differences between children from rural and urban elementary schools. Behavior of time using mobile phones, body position, alignment and distance of the mobile phone to the head or eye, the purpose, tool and the place where to use the cellphone, both groups have the same percentage. Conclussion: there are differences and similarities in behavior in using mobile phones between children from rural and urban elementary schools.